Linkage between Supply Chain Operation Reference model and Learning Style Diversity- An Empirical Study in Indian Logistics Industry - Pooja Tiwari; Dr. Shalini Srivastava; Dr. Vikas Garg (International Journal of Supply Chain Management, 2019)
Due to intense competition and dynamism in the environment the concept of psychological diversity has attracted the attention of many researchers. Earlier, the concept of surface level diversity has gained the attraction of many researchers but now slowly and gradually psychological diversity i.e. learning style diversity has gained attention. Based on the available literature, it is implied that learning style of the individual influences the different stages of the team learning process. It has been analyzed that due to advancement in technology and transformation in logistics industry, diversity at workplace has become a key priority for the logistics and supply chain management industry. People from diverse background such as driver, planners, warehouse operators etc. are performing the job. It has been analyzed that logistic companies mange relation globally and so the level of diversity is very high in logistic industry. According to available literature, the relationship between learning diversity and the different stages of the learning process was examined and authors were interested to explore the relationship between different variables. To collect the data mix method has been used i.e. both qualitative and quantitative method is adopted and under this questionnaire method has been adopted by the researcher. To conduct the study 377 respondents working in 36 teams in 16 organizations as middle level managers in an Indian logistic industry have been considered and also the interview of 36 team leaders has been taken to study the phenomena in detail. The data is analyzed by the correlation method and codifying the interview. Finding of the research suggested that some of the team learning stages is influenced by the learning style of the individual and due considerations should be taken during the forming stage of the team .The study is being conducted to explore the role of learning style diversity in logistic companies and how it is influencing the different stages of supply chain operation reference model which is referred as team learning process in current study. According the study findings it has been understood that the logistic companies are taking various strategic initiatives to address surface level diversity, company should also focus on deep level or psychological diversity. The current study will be highly beneficial for the logistic industry to understand the implication of psychological aspect Current study has only considered the middle level managers working so future studies can be conducted by considering the other aspects of logistic industry. Keywords: Learning style diversity, Team learning process, team performance.